Particle breakage - Salman, A. D.; Ghadiri, M.; Hounslow, M. J. (Michael J.); ScienceDirect eBooks (Amsterdam ; Oxford : Elsevier, 2007)
Particle breakage is an important process within a wide range of solids processing industries, including pharmaceuticals, food, agricultural and mining. Breakage of particles can be defined as intentional and unintentional, depending on whether it is desired or not. Through understanding of the science and underlying mechanisms behind this phenomenon, particle breakage can be either minimised or encouraged within an efficient and effective process. Particle Breakage examines particle breakage at three different length scales, ranging from single particle studies through groups of particles and looking at solid processing steps as a whole. This book is the widest ranging book in the field and includes the most up-to-date techniques such as Distinct Element Method (DEM), Monte Carlo simulations and Population Balance Equations (PBE). This handbook provides an overview of the current state-of-the- art and particle breakage. From the small scale of a single particle, to the study of whole processes for breakage; both by experimental study and mathematical modelling. * Covering a wide range of subjects and industrial applications * Allows the reader an understanding of the science behind engineered breakage processes * Giving an unrestrictive and interdisciplinary approach.
I. Fundamental -- 1. Breakage of single particles: Quasi-static -- (L. Marcelo Tavares). -- 2. Impact breakage of single particles: Double Impact Test (K.T. Chau, S.Z. Wu). -- 3. Particle breakage due to bulk shear (J. Bridgwater). -- 4. The principles of single-particle crushing (G. Unland). -- II. Milling -- 5. Rotor impact mills (R. Nied). -- 6. Wet grinding in stirred media mills (A. Kwade, J. Schwedes). -- 7. Roller milling of wheat (G.M. Campbell). -- 8. Air jet milling (A. Chamayou, J.A. Dodds). -- 9. Breakage and morphological parameters determined by laboratory tests (M. Yekeler). -- 10. Selection of fine grinding mills (Toyokazu Yokoyama, Yoshiyuki Inoue). -- 11. Fine grinding of materials in dry systems and mechanochemistry (Qiwu Zhang et al.). -- 12. Comminution energy and evaluation in fine grinding (Yoshiteru Kanda, Naoya Kotake). -- 13. Enabling nanomilling through control of particulate interfaces (M. Sommer, W. Peukert). -- 14. Analysis of milling and the role of feed properties (Mojtaba Ghadiri et al.). -- III. Modelling -- 15. Monte Carlo method for the analysis of particle breakage (B.K. Mishra). -- 16. Numerical investigation of particle breakage as applied to mechanical crushing (C.A. Tang, H.Y. Liu). -- 17. The cohesion of fractal agglomerates: an elementary numerical model (E. Pefferkorn). -- 18. The linear breakage equation: from fundamental issues to numerical solution techniques (M. Kostoglou). -- 19. Analysis of agglomerate breakage (M. Ghadiri et al.). -- 20. Modelling of mills and milling circuits (P. Toneva, W. Peukert). -- IV. Applications -- 21. Particle strength in an industrial environment -- (Dr. G.M.H. Meesters). -- 22. The strength of pharmaceutical tablets (I.C. Sinka et al.). -- 23. Crystal growth and dissolution with breakage: distribution kinetics modelling (Giridhar Madras, B.J. McCo). -- 24. Liberation of valuables embedded in particle compounds and solid waste (W. Schubert, J. Tomas). -- 25. Attrition in fluidised beds (R. Boerefijn et al.). -- 26. A mechanistic description of granule deformation and breakage (Y.S. Cheong et al.). -- 27. Descriptive classification: failure modes of particles by compression (I. Gabbott et al.). -- 28. A new concept for addressing Bulk Solids Attrition in Pneumatic Conveying (L. Frye).
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Powders; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Powders; Electronic books